Literasi Keuangan Syariah Dengan Tema Manfaat Pinjaman Online Untuk Mendukung Perekonomian Ibu-Ibu PKK Di 16c Metro Barat - Vera Ismail; Alvina Dewanti; Diah Ratna Sari; Nabila Nur Amaliah; Rini Payu Lestari; Sindi Fatica Sari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
The development of globalization in several developed countries is very fast and has even entered the 5.0 era and Indonesia itself is in the category of countries that are quite lagging behind in terms of globalization so that it is still surviving in the industrial era 4.0. Digital and technology have replaced the role of humans in almost all fields and have used online versions such as markets (e-commerce), banks (m-banking), classes (virtual meetings), and others. In fact, the digital aspect has entered the financial industry (services) which is better known as Financial Technology, hereinafter referred to as Fintech. Peer to peer lending as a form of financial technology (fintech) is the result of technological advances which offer many loans with easier and more flexible terms and conditions compared to conventional financial institutions such as banks.